Respuesta :
I'll use x, y, and z for the numbers
x + z = y
x + y = 6 + z
3x - 2y = z
Substitute (x + z) for y in the second equation.
x + (x + z) = 6 + z and solve
2x = 6
x = 3
Rearrange another equation and substitute (3) for x.
(3) + y = 6 + z solve for y
y = 3 + z
substitute y in another equation
3(3) - 2(3+z) = z solve
9 - 6 - 2z = z
3 = -z
z = 3
going back to the first equation:
x+z=y
3 + 3 = 6
Answers:
x=3
y=6
z=3
check all equations to make sure it works for all equations
x + z = y
x + y = 6 + z
3x - 2y = z
Substitute (x + z) for y in the second equation.
x + (x + z) = 6 + z and solve
2x = 6
x = 3
Rearrange another equation and substitute (3) for x.
(3) + y = 6 + z solve for y
y = 3 + z
substitute y in another equation
3(3) - 2(3+z) = z solve
9 - 6 - 2z = z
3 = -z
z = 3
going back to the first equation:
x+z=y
3 + 3 = 6
Answers:
x=3
y=6
z=3
check all equations to make sure it works for all equations
Answer:
8
Step-by-step explanation:
Let the first number be x
Let the second number be y
Let the third number be z
According to question
First number + third number= second Number
x + z = y equation (1)
first number + second number = 6 more than third number
x + y = 6 + z equation(2)
Put y = x + z in equation (2)
x + x + z = 6 + z
2 x = 6
x = 3
now , y = 3+z
3 times first number - 2 times second number= third number
3 x - 2 y = z equation (3)
put y = 3 +z in equation (3)
3× 3 - 2(3+z) = z
9 - 6 -2 z = z
z+2 z= 3
3 z= 3
z= 1
Now, y = 3+1= 4
Sum of x ,y and z
x+y+z= 3+4+1= 8
Hence, the correct answer is 8